Media and Journalists in Twitter: The Chilean Case - López-Hermida Russo, Alberto (2011)
Social networks like Twitter have become platforms used by people as well as corporations to reach audiences of a size that, barely a decade ago, seemed unimaginable. Journalism has also been affected by this trend, so now journalists and media corporations make use of these social networks. The presence of media and journalists in platforms such as Twitter inevitably comes with multiple ways of presenting themselves to the public. While the media face the challenge to upkeep their informational end, journalists have to find a balance between their personal and professional profile. A comparative usability analysis of journalists and media Twitter accounts makes this an evident problem that will allow studying the phenomenon and proposing certain guidelines for action. Questions emerge rapidly: Can media corporatize a social tool that is essentially personal? Must a journalist inform, give his/her opinion as a common citizen, in an account created under his professional profile? Can media and journalists profiles co-exist in the same social network? The answers to these questions present us with new professional and ethical challenges that are worthy of further study.